The Meaning of Tolaki, Minangkabau, and Timor Cultural Symbol in Three Nusantara Folklores: Oheo, Kaba Malin Deman, and Tujuh Bidadari - Priventa, Hendrike; Noor, Redyanto (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Indonesian are less aware of the function of folklore in the modern era. When examined more deeply, folklore is a manifestation of local cultural values ​​that are not widely known. This is the background for the research of this article which intends to introduce the uniqueness of the Nusantara folklore through an analysis of the eating of cultural symbols. The purpose of this research is to describe and introduce the meaning of cultural symbols in the Nusantara folklore. The method used is literature using semiotic theory. The results obtained in this study are as follows. 1) Folklore is part of a culture, therefore in the structure of folklore found cultural elements represented in the form of symbols. 2) Cultural symbols in folklore cannot be interpreted directly, with a semiotic and cultural approach symbols can be interpreted according to the cultural origin of the folklore. 3) Literature, culture, and art are three things that cannot be separated. Cultural symbols do not only show cultural elements but also provide a moral message and aesthetic side in reading literary works. 4) Folklore can become an identity in culture from that it can be drawn that cultural symbols can show the progress of civilization in a culture. 5) The three folklores of the archipelago that have been studied have their own characteristics. Oheo with the influence of the elements of marriage and social stratification, Kaba Malin Deman with a touch of matrilineality, and Tujuh Bidadari with the influence of religious elements